2022 MEDAM Assessment Report on Asylum and Migration Policies in Europe. Refugee protection in the EU: Building resilience to geopolitical conflict - Silvia Carta; Helena Hahn; Tobias Heidland; Paweł Kaczmarczyk; Matthias Lücke; Karolina Łukasiewicz; Mehari Taddele Maru; Marta Pachocka; Martin Ruhs (Kiel Institute for the World Economy (IfW Kiel), 2022)
In this MEDAM Assessment Report, we review EU policy developments-both in response to recent geopolitical conflicts and with respect to the broader reform agenda for the EU asylum system. We then turn to the reception and hosting of refugees from Ukraine in the EU member states-focussing on the situation in Poland. At the same time, it remains a long-term challenge to understand and manage migration to Europe from Africa. We report MEDAM research findings on the decision-making behavior of potential migrants, the links between migration prevalence and improving living conditions in low- and middle-income countries, and cooperation on migration management between the European Union and African Union. The 2022 MEDAM Assessment Report concludes six years of research, policy analysis, and interaction with stakeholders by the Mercator Dialogue on Asylum and Migration in Europe (MEDAM). – – In diesem MEDAM Assessment Report analysieren wir die politischen Entwicklungen der EU - sowohl als Reaktion auf die jüngsten geopolitischen Konflikte als auch im Hinblick auf die umfassendere Reformagenda für das EU-Asylsystem. Darüber hinaus, betrachten wir die Aufnahme von Flüchtlingen aus der Ukraine in den EU-Mitgliedstaaten- mit Schwerpunkt auf der Situation in Polen. Gleichzeitig bleibt die langfristige Herausforderung, die Migration aus Afrika nach Europa besser zu verstehen und zu steuern. Wir berichten über MEDAM-Forschungsergebnisse zum Entscheidungsverhalten potenzieller Migrantinnen und Migranten, zu den Zusammenhängen zwischen Migrationsprävalenz und der Verbesserung der Lebensbedingungen in Ländern mit niedrigem und mittlerem Einkommen sowie zur Zusammenarbeit bei der Migrationssteuerung zwischen der Europäischen Union und der Afrikanischen Union. Der MEDAM-Sachstandsbericht 2022 schließt sechs Jahre Forschung, Politikanalyse und Interaktion mit Interessengruppen durch den Mercator Dialogue on Asylum and Migration in Europe (MEDAM) ab.
Keywords: 320; Asylum and refugee policy; Ukraine; Temporary Protection Directive